A Team-based Approach to Development - Katherine Frank; Kristi Haik; Kelly Jones (Academic Chairpersons Conference Proceedings, 2016)
This workshop focuses on strategies for engaging in successful short- and long-term development and fundraising efforts at the program and department level, while remaining aligned with college and university priorities. Facilitators include a chairperson, director of college development, and dean.
Keywords: Development; fund-raising; planning; collaboration; marketing